Lightweight Composite Microwave Absorbing Materials Based on Graphene Aerogels with Honeycomb Structure. Issue 8 (30th April 2019) - Shi, Kouzhong; Li, Jun; Wu, You; Bai, Han; Hong, Yang; Zhou, Zhongxiang
Abstract : Porous graphene‐based composites offer immense potential for microwave absorption because of their light weight and high performance. In this work, a honeycomb structure filled with porous graphene is demonstrated with excellent radar‐absorbing properties. This graphene‐based composite reaches the maximum reflection loss (RL) of −15 dB at 8.8 GHz with only a thickness of 4.0 mm and an areal density of 0.26 kg m −2 . Raman spectroscopy confirms the existence of graphene and scanning electron microscopy images reveal how these large graphene flakes are arranged to a three‐dimensional porous structure. In addition, a monolithic porous graphene aerogel, without the honeycomb core, and a RL simulation of it are also investigated for comparison, which reveals antipodal properties. This work shows that the insulated honeycomb structure increases the surface characteristic impedance of the whole composite material, which mainly contributes to the reduction of total reflection from the interface. Various structural influence factors have been analyzed, the results provide a new idea for exploring high‐performance microwave absorbers of graphene‐based materials. Abstract : A lightweight honeycomb structure filled with porous graphene aerogel is demonstrated with excellent radar absorbing properties. It reaches the maximum reflection loss (RL) of −15 dB at 8.8 GHz with only a thickness of 4.0 mm and an areal density of 0.26 kg m −2 . This study shows that loose porous aerogel structures and insulated honeycomb cores themselves play a key role in improving the microwave absorption properties of composites.